2019
DOI: 10.1080/10942912.2019.1593193
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of coffee against colorectal cancer and hepatocellular carcinoma

Abstract: Cancer is a complex and evolving disease that is the leading cause of death in the twenty-first century, and colorectal and liver cancers specifically are in the top 10 cancer types in terms of incidence and mortality; therefore, there has been a shift towards researching prevention strategies, amongst which chemoprevention is key. Coffee is a natural product that has recently gained importance in this area due to its chemopreventive potential and its high level of consumption worldwide. In this review, recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Nevertheless, experimental evidence that the protective effect of coffee components on NAFLD is related to antioxidant effects is still unclear [180,183]. It has been reported that CGA protects against palmitate-induced ER stress and apoptosis in vitro [178,184]. Moreover, based on experimental models of high-fat-/high-carbohydrate-induced NALFD, it has been reported that CGA exhibits hepatoprotective effects, including improvement of metabolic function, reducing inflammation, and improving liver histology [185].…”
Section: Coffee Components: Caffeine and Coffee Polyphenolsmentioning
confidence: 99%
“…Nevertheless, experimental evidence that the protective effect of coffee components on NAFLD is related to antioxidant effects is still unclear [180,183]. It has been reported that CGA protects against palmitate-induced ER stress and apoptosis in vitro [178,184]. Moreover, based on experimental models of high-fat-/high-carbohydrate-induced NALFD, it has been reported that CGA exhibits hepatoprotective effects, including improvement of metabolic function, reducing inflammation, and improving liver histology [185].…”
Section: Coffee Components: Caffeine and Coffee Polyphenolsmentioning
confidence: 99%
“…[52] Sustainability Practices of small farmers for climate change mitigation. [53] Health Coffee's role against the apparition of colorectal and liver cancer. [54] Quality Storage of coffee crop (hermetic bags) for preserving the quality.…”
Section: Referencementioning
confidence: 99%
“…Although different studies have reported several biological properties of CGA [ 43 , 44 ], there still needs to be clear evidence about the role of this natural compound in CRC. In the present study, we showed that CGA induced ROS production and mitochondrial hyperpolarization, which results in the DNA fragmentation and reduced cell viability of colon cancer cells, which harbors alterations in the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%